KERJASAMA INDONESIA-SELANDIA BARU PADA SEKTOR PETERNAKAN SAPI PERAH DAN INDUSTRI PENGOLAHAN SUSU - Didi Triyanto Alfiah; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
One component of farm sub-sector that has much benefits and potentially to be developed in indonesia is a dairy agribusiness. Geography, ecology, and so of fertility land in some regions in indonesia having characteristics that suitable for the development of dairy agribusiness. In addition, from the demand side, milk production in the country is still not enough to cover needs of domestic millk consumption. Currently in domestic milk production can not meet more than 30 % of the national demand the remaining, 70 % derived from imports.Dairy development in indonesia cannot be separated from the problems that impede the development of the dairy. Most of the business of a farm of dairy cattle managed by with a scale business that is not economical. In fact, dairy farm business is people, faced with two major problems, namely the problem zooteknik in the face of the global market as well as socio-economic issues that are less institutional support to business performance.To overcome the problem, the indonesian government take measures to save and improve the business of a farm of dairy industry in indonesia. One way to be taken is to have a partnership with the countries that have been successful in doing application of technology dairy farm as New Zealand.In the treaty the new zealand government will help improve the human resources ( HR ), quality and quantity of farmers of dairy industry indonesia by providing training, the scholarship, consultation, dairy processing plant, processing plant even the management of a farm that has successfully implemented in the country.Keyword : Dairy, Indonesia, New Zealand, Milk, Farm, Agribusiness